English Teachers’ Perception at Junior High School Level on The Implementation of Kurikulum Merdeka in Banjar District - Raudah, Siti; Noor, Pajrian; Najmiah, Lailatun (Linguistics and ELT Journal, 2024)
Curriculum revisions are nothing new in Indonesia. Three curricular revisions have occurred throughout last two decades. Finally, the post-Covid-19 emergency curriculum was changed to Independent Curriculum, which purportedly streamlines K13. Merdeka Curriculum is only one year old, of course it still requires adjustments, especially in implementation. For this reason, researchers decided to examine teachers' perceptions (as the front guard of education) regarding the Independent Curriculum which focuses on implementation in teaching English at junior high school level in Banjar Regency, including regarding obstacles in implementation. This research uses descriptive qualitative with interviews as the data collection method. The type of interview used was semi-unstructured in-depth interview with 7 English teachers in 4 Junior High Schools in different sub-districts in Banjar District which implemented Merdeka Curriculum as respondents, determined using purposive sampling method. Following the investigation, respondents acquired 9 positive and 8 negative perceptions. According to the teacher's perception, Independent Curriculum has evolved to the times with usage of digital media/internet as a learning ied, making learning resources more abundant, there are also fun projects students can do, Aside from that, this curriculum is thought to be more supportive of students by using terms like student center, positive discipline, and differentiation approach, which allows teachers to provide more opportunities for students develop themselves by understanding them personally and providing comfortable environment. The obstacles encountered are mostly related to the facilities, teacher readiness, and increasingly limited time due to large number of tasks that teachers must complete as result of this curriculum..